Utilization of Call Data Record (CDR) Analysis Techniques in Online Fraud Investigations by the Salatiga Police Resmob Satreskrim Unit - Dhimas Abie Thoyib (Indonesian Journal of Police Studies, 2021)
The Industrial Revolution 4.0 brings progress in the field of technology that must be utilized properly by the Police as law enforcers in carrying out their duties in the field. Researchers see that there is a criminal act that has not paid attention to its disclosure on the grounds of the lack of witnesses and evidence as well as the location of the fictitious perpetrator. The crime is a crime of online fraud. Based on the background of the problem and the research conducted, the author will explain the crime of online fraud on behalf of the Mayor of Salatiga with a criminal penalty of Article 378 of the Criminal Code by investigators, the use of CDR analysis techniques with postal check applications used by investigators, and the factors that influence the use of analytical techniques. CDR is in the investigation of online fraud by the Criminal Investigation Unit of the Salatiga Police Satresmob. The results of this study are online fraud crimes on behalf of the Mayor of Salatiga are subject to Article 378 of the Criminal Code but it would be more appropriate if they were subject to Article 28 paragraph (1) of the ITE Law which is more burdensome for the perpetrators. The CDR analysis technique has been put to good use in investigating online fraud crimes on behalf of the Mayor of Salatiga, but the tracking technology is only limited to knowing the BTS location from the perpetrator's phone number, so technology development such as the use of the "Direction Finder" tool is needed. The use of CDR analysis techniques is influenced by several factors, namely the quality of human resources, investigation budget, investigation infrastructure, cell phone numbers, calling activities, collaboration with MC Polri and Telecommunication Service Providers. So it is necessary to improve the quality of human resources, investigative budgets, investigative infrastructure, record call data, collaborate with MC Police and Providers so that CDR analysis techniques can be utilized more optimally in any online fraud investigation.